Nephroprotective Effect of Pentoxyphylline Through Improvement in the Expression of TGF-beta1, Collagen Type-1, and Renal Interstitial Fibrosis in Swiss Strain Mice After Being Induced by Doxorubicin - Bambang Purwanto; A Guntur Hermawan (The Indonesian Biomedical Journal, 2010)
BACKGROUND: Use of doxorubicin (DXR) in the treatment of cancer has been increasing along with the increase in cancer morbidity. Nephrotoxic effects of DXR are still a problem. Pentoxyphylline (PTX) as an electron-donor material can be nephroprotective, so the combination of DXR and PTX might reduce the nephrotoxic effects of DXR. The aim of this study was to prove the nephroprotective effect of PTX and DXR nephrotoxicity through the improvement of TGF-β1, collage type-1, and renal interstitial fibrosis.METHODS: Twenty-four males Swiss strain mice, divided into three groups namely Control (C) injected with NaCl 0.9%; DXR induced nephrotoxicity (D); and effect of PTX on D (P/D) by intraperitoneally, respectively, each group consisted of 8 mice. Injections were given once a week for three consecutive weeks. At 8th week post-treatment, all eight mice of each group were sacrificed. Examination of TGF-β1 and collagen type-I expression was done by immunohistochemistry with monoclonal antibody. Renal interstitial fibrosis examination was done by a histopathologist, using Verheoff van Giesen staining. The statistic analysis was carried out using one-way ANOVA.RESULTS: TGF-β1 expression increased from C to D and subsequently decreased in P/D (4.50±3.89 vs. 177.88±68.78 vs. 36.88±9.51). Collagen type-I expression increased from C to D and subsequently decreased in P/D (12.00±14.32 vs. 186.25±125.62 vs. 36.00±29.14). Renal interstitial fibrosis expression increased from C to D and subsequently decreased in P/D (16.75±6.14 vs. 85.00±7.33 vs. 60.50±11.40). The expression of TGF-β1, collagen type-1, and renal interstitial fibrosis were higher significantly in D group as compared to C group (p<0,001). The expression of TGF-β1, collagen type-1, and renal interstitial fibrosis were lower significantly in P/D group as compared to D group (p<0.005).CONCLUSIONS: PTX was proved to be nephroprotector inducing by DXR.KEYWORDS: PTX, nephroprotector, TGF-β1, collagen type-I, renal interstitial fibrosis